Quality of Biocompost Resulting from Biopore Holes Based on Light Intensity and Acidity Degree (pH) - Arik Pujiyanti; Sulhadi Sulhadi; Mahardika Prasetya Aji (Journal of Natural Sciences and Mathematics Research, 2019)
The use of chemical fertilizers that are not balanced with the provision of organic fertilizers can damage the soil. Chemical fertilizers can also damage the balance of nutrients in the soil and lower soil pH. Therefore, organic fertilizers are needed to help restore soil fertility and LRB as a medium for composting organic fertilizers. The biopore infiltration hole (LRB) is "activated" by providing organic waste. This waste will be used as a source of energy for soil organisms to carry out their activities through the decomposition process. This decomposed waste is known as compost. Compost is a term for man-made organic fertilizer made from the decomposition process of the remains of living things (plants or animals). The investigation of this study was to determine the quality of compost based on light intensity and acidity (pH) from the results of biopore infiltration holes (LRB) as well as good physical properties of compost. This type of research is an experimental research. Good quality compost has low resistance. The pH value of the compost in samples A,B,D,E is 6.5-7.5 so it is neutral, while the pH of the compost sample C is 8.5 is alkaline. The intensity of the light is high. The results of the lowest light intensity in the compost from this study were leaf compost + sawdust + EM4 of 990 lux, fermented in LRB for 2 weeks. Meanwhile, the highest light intensity value was found in the compost of raw material leaves which were fermented for 1 month at 1017 lux. So the greater the value of light intensity in the compost, the better quality it has, because it can improve soil fertility. ©2019 JNSMR UIN Walisongo. All rights reserved.